2001
DOI: 10.1034/j.1600-0447.2001.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related differences in the onset of panic disorder

Abstract: Premorbid clinical conditions of PD seem to differentiate between males and females in the role of precipitating events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
3
15
1
Order By: Relevance
“…However, in our study, as it was purported to compare the males and females for Axis I and Axis II coexistence, it was observed that the number of persons in each group are equal. The fact that there was no significant difference in statistical sense in our study complies with the literature information noting that there is no difference between the genders for this purpose (11,20). It is seen from the Chart 1 that the education level of the females are significantly lower than that of males.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, in our study, as it was purported to compare the males and females for Axis I and Axis II coexistence, it was observed that the number of persons in each group are equal. The fact that there was no significant difference in statistical sense in our study complies with the literature information noting that there is no difference between the genders for this purpose (11,20). It is seen from the Chart 1 that the education level of the females are significantly lower than that of males.…”
Section: Discussionsupporting
confidence: 88%
“…It is seen from the Chart 1 that the education level of the females are significantly lower than that of males. The non compliance of such result of our study with the findings of the studies indicating that there were no differences between the genders from the point of the level of education (11,21), or that the females with PD had higher education level (20) can be explained with the fact that in our society, the education level of the females are lower in general.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations